Case series: the application of "third wave" cognitive behavioural therapies in difficult to treat asthma. (21st October 2015) - Fellows, Jodie Louise; Flower, Laura; Blakey, John; Kurukulaaratchy, Ramesh; Howard, Ruth; Mansur, Adel
Abstract: Objective : This paper provides for the first time cases of individual psychological therapy undertaken in tertiary, difficult to treat asthma services using "third wave" cognitive behavioural therapy (CBT) approaches. Methods : These cases were selected to represent common psychological presentations in difficult to treat asthma clinics, namely denial of severity and over-identification with asthma. Assessment, formulation, intervention and results are outlined. Results : Case 1 demonstrated change from severe to mild depression and anxiety, reduction in shame and improved well-being. Case 2 demonstrated improvements in well-being and psychological symptoms. Both interventions were experienced by the patients as highly satisfactory. Conclusions : It is concluded that a psychological understanding of patients' presentations can open up new avenues for intervention. Further research into the potential utility of third wave cognitive therapies in difficult to treat asthma is warranted.